Heterogeneous Marandu grass (Urochloa brizantha) pastures under continuous stocking enhance dry matter intake in sheep - Silva, Jhonatan Gonçalves; Pedro da Silva, Simone; Andrade Reis, Laura; Cleber Souza silva, Yuri; Celso Oliveira Moura Junior, Romario; Almeida Marques da Silva, Natascha; De Lima Macedo Junior, Gilberto; Rozalino-Santos, Manoel-Eduardo (Revista Colombiana de Ciencias Pecuarias, 2025)
Background: Pasture structure directly influences the ingestive behavior and feed intake of grazing ruminants, particularly under continuous stocking systems. More heterogeneous swards, with greater variability in plant height, may increase selectivity and alter intake dynamics and feeding efficiency. Objective: To evaluate how different horizontal structures of marandu grass (Urochloa brizantha cv. Marandu) pastures, maintained at an average height of 25 cm, affect feeding behavior and nutrient intake by sheep.Methods: The study was conducted from September 2019 to March 2020, using 16 crossbred sheep (Santa Inês × Dorper) allocated to eight paddocks under two treatments: 1) less heterogeneous pasture (plant height CV <35%) and 2) more heterogeneous pasture (CV >35%). Variables evaluated included nutrient intake, digestibility, feeding behavior (grazing, rumination, idleness, meal time, number and interval between meals, and rumination bouts), as well as forage mass, morphological composition, and chemical composition of the pasture. Data were analyzed by analysis of variance (ANOVA), using the F test at a 10% probability level (P<0.10).Results: More heterogeneous swards promoted greater dry matter intake by grazing sheep (P<0.10). However, pasture heterogeneity did not significantly affect nutrient digestibility, chemical composition of hand-plucked samples, or behavioral parameters (P>0.10).Conclusion: Under continuous stocking, marandu grass pastures with higher structural heterogeneity (CV between 50.32% and 60.64%) increase dry matter intake in sheep. Although heterogeneity did not influence digestibility or quantitative aspects of behavior, animals showed more frequent grazing during the day and concentrated rumination and idleness at night under the same experimental conditions